PENGEMBANGAN INSTRUMEN SOAL HIGH ORDER THINKING SKILLS PADA PEMBELAJARAN TEMATIK KELAS V SEKOLAH DASAR - Dhea Ananda; Kartono Kartono; Dyoty Auliya Vilda Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis development research was carried out to produce a produc in the form of a question instrument based on high order thinking skills in class V theme 3 subtheme 1. The research method used is research and development (R&D) adaptation of research development by Borg & Gall which includes the following steps: research and information collection, planning, early product development, initial field trials, major product revisions, field trials, and operational product revisions. The data sources of this research were 54 students of Muhammadiyah 2 Elementary School. The data collection instruments in this study consisted of interviews, questionnaires, and tests in the form of HOTS questions. The data analysis technique used in this research is item analysis. The results of the study indicate that the HOTS-based question instrument consists of 20 multiple-choice questions from the material, construction, and language aspects, which are valid and worthy of testing. The instrument consisting of 20 items has a validity level of 0.5097 (valid), the degree of reliability is 0.893 (high). Based on the level of difficulty and distinguishing power of the 20 items, there are 19 items that match the characteristics of HOTS.Keywords: Development, Instrument, High Order Thinking Skills.